A double-edged sword role of IFN-γ-producing iNKT cells in sepsis: Persistent suppression of Treg cell formation in an Nr4a1-dependent manner - Yingyu Qin; Yilin Qian; Shengqiu Liu; Rong Chen (iScience)
Summary: Sepsis, a leading cause of mortality in intensive care units worldwide, lacks effective treatments for advanced-stage sepsis. Therefore, understanding the underlying mechanisms of this disease is crucial. This study reveals that invariant natural killer T (iNKT) cells have an opposing role in the progression of sepsis by suppressing regulatory T (Treg) cell differentiation and function. The activation of iNKT cells by α-Galcer enhances interferon (IFN)-γ production. Blocking antibodies or transferring IFN-γ-deficient iNKT cells demonstrates that iNKT cells inhibit Treg differentiation through IFN-γ production. Additionally, iNKT cell-mediated Treg inhibition prevents secondary infection caused by Listeria monocytogenes during the post-septic phase. The transcriptomic analysis of Treg cells further reveals that the suppressive function of Tregs is impaired by iNKT cells. Finally, we demonstrate that iNKT cells inhibit Treg differentiation in an Nr4a1-dependent manner. Our data uncover the dual function of iNKT cells in sepsis progression and provide a potential treatment target for this adverse long-term outcome induced by sepsis.